Studies on Effect of Application of Capric Acid and Stearic Acid based Reactive Phase Change Materials (rPCM) with PHAMS Binder on Thermal Comfort of Cotton Khadi Fabric as Thermo-tropic Smart Textiles. Issue 13 (1st December 2022) - Kar, Tapas Ranjan; Samanta, Ashis Kumar; Sinnur, H. D.; Kumar, Mahesh
ABSTRACT: Studies on effect of capric acid and stearic acid based reactive phase change materials (rPCM) on physical properties and thermal comfort of cotton khadi fabric are reported by direct application of Capric acid (CA) and Stearic Acid (SA) as rPCM with Poly-Hydroxy-Amino-Methyl-Silicone reactive binder and MgCl2 as catalyst by simple pad-dry-cure technique (instead of cumbersome and costlier microencapsulation) which are embedded under PHAMS reactive binder film. Thermal characterization of pure Capric acid (CA), pure Stearic acid (SA) and mixture of each with PHAMS binder treated cotton substrate were carried out by cryogenic DSC at 0–100°C and at also at ambient (30°C) to 500°C. Between these two PCM materials, Capric Acid (CA) shows superior results. Amongst different concentrations of CA, 4% CA applied on Cotton khadi fabric with 2% PHAMS binder and 1 /5 th (on weight of PCM material) of MgCl2 catalyst shows good thermo-regulating character in cotton khadi fabric showing freezing temperature (Tf ) 8.3°C, Melting Temperature (Tm ) 22.6°C with melting enthalpy 34.1 J/g and freezing enthalpy 36.5 J/g . water vapor transmission value of 28.3 gm/hour/m 2 and air permeability value of 262.3 ft 3 /ft 2 /min, showing favorable thermal comfort, enabling storage and release of heat energy to improve the thermal comfort with changing environmental conditions.